2022
DOI: 10.1093/plphys/kiac399
|View full text |Cite
|
Sign up to set email alerts
|

γ-Aminobutyric acid may directly or indirectly regulate Arabidopsis ALMT9

Abstract: The mechanism by which GABA regulates stomatal pore aperture and anion transport activity of ALUMINUM-ACTIVATED MALATE TRANSPORTER 9 is debated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Additionally, ABA enhances the synthesis of osmoprotectants, which help plants withstand harsh environmental conditions [ 4 ]. Recent research has revealed that GABA can modify the activity of ALUMINUM-ACTIVATED MALATE TRANSPORTERS (ALMTs), which are implicated in aluminum tolerance, root growth, pollen tube growth, and stomatal pore regulation [ 44 ]. These findings provide valuable insights into the mechanism by which GABA acts as a membrane potential-based signal, connecting plant metabolic status with various physiological processes [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ABA enhances the synthesis of osmoprotectants, which help plants withstand harsh environmental conditions [ 4 ]. Recent research has revealed that GABA can modify the activity of ALUMINUM-ACTIVATED MALATE TRANSPORTERS (ALMTs), which are implicated in aluminum tolerance, root growth, pollen tube growth, and stomatal pore regulation [ 44 ]. These findings provide valuable insights into the mechanism by which GABA acts as a membrane potential-based signal, connecting plant metabolic status with various physiological processes [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Note that, a second study failed to detect GABA-mediated anion transport through ALMT9 in a patch-clamp experiment when GABA was applied from the cytosolic or the vacuole sides ( Jaślan and De Angeli, 2022 ). This study was, however, criticised by the authors of the GABA-stomatal regulation study based on the nature of the ALMT9 expressed (GFP tag), the cell type it was expressed in (mesophyll cells), and the nature of the orthologous system ( Nicotiana benthamiana ) ( Gilliham and Xu, 2022 ). Hence, whether GABA acts directly or indirectly on ALMT9 is still an open question.…”
Section: Gabamentioning
confidence: 99%